Study of Youths' Knowledge, Behavior, and Attitude towards Consanguineous Marriages - M Hasanzadeh-Nazarabadi; GH Rezaeetalab; F Dastfan (Tehran University of Medical Sciences, 2006)
Consanguineous marriages are traditionally favoured in most of Asian and African countries especially in the Muslim countries. However, it is apparent that these kinds of marriage are a major factor of some genetic disorders inherited in an autosomal recessive pattern. Although there is a long history of consanguineous marriage in Iran, the information on its prevalence is too poor. The aim of this study was to define the frequency of consanguineous marriage in Mashhad City, Khorasan Province, Iran as well as its correlations to the youths' attitude and their knowledge about the genetic consequences of inbreeding. The concerning information was obtained by administration of a direct questionnaire including 50 open and closed questions. The subjects were 500 young people (with a mean age of 21.4 yr) who were selected during a quota sampling. The results of this study revealed that most of the youth did not have favorable information about the consequences of genetic disorders of inbreeding. There was a higher rate of consanguinity in the rural rather than the urban population. The traditional beliefs and the authority of the parents who had also experienced consanguineous marriage were other predominating factors of inbreeding.